2021
DOI: 10.3390/foods10020403
|View full text |Cite
|
Sign up to set email alerts
|

Coriandrum sativum L.—Effect of Multiple Drying Techniques on Volatile and Sensory Profile

Abstract: Coriandrum sativum L. is a medicinal and aromatic plant spread around the world, with beneficial properties that are well recognized. Both coriander seeds and leaves are used for pharmaceutical and flavoring purposes. Even though coriander seeds tend to be more popular, the leaves are receiving a consistently growing interest, especially because of popularization of Mexican, Northern African, and Indian cuisines. This increased attention brings about the necessity for providing the product with guaranteed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Applied heat treatment, especially vacuum cooking, resulted in the degradation of volatile compounds associated with freshly cut grass or leaf notes. This is consistent with the results of Łyczko et al [40], who found that even slight drying of fresh cilantro at 50 • C significantly decreases (Z)-Hex-3-en-1-ol and (E)-Hex-2-en-1-ol, and the effect is more notable with higher thermal treatment. The disappearance of almost all the compounds of the "green" note was not only observed during the drying process but also for blanching of the basil [41].…”
Section: Effect Of Various Heat Treatment Methods On the Aroma Profile Of Basil Infusionssupporting
confidence: 93%
“…Applied heat treatment, especially vacuum cooking, resulted in the degradation of volatile compounds associated with freshly cut grass or leaf notes. This is consistent with the results of Łyczko et al [40], who found that even slight drying of fresh cilantro at 50 • C significantly decreases (Z)-Hex-3-en-1-ol and (E)-Hex-2-en-1-ol, and the effect is more notable with higher thermal treatment. The disappearance of almost all the compounds of the "green" note was not only observed during the drying process but also for blanching of the basil [41].…”
Section: Effect Of Various Heat Treatment Methods On the Aroma Profile Of Basil Infusionssupporting
confidence: 93%
“…Those results correspond to numerous studies referring to drying technology, where FD is very often treated as the reference drying method [1,46]. In terms of the destructive influence of particular drying methods, it has been proven before that it is impossible to point out undoubtedly which drying method is the less optimal one [47,48]; it has always been dependent on the object of the study. In the case of sweet potato with kale, onion, or sodium chloride addition, it may be concluded that FD or VD should be applied; however, it has to be highlighted that onion addition has some unexpected influence on the VOC retention.…”
Section: Aroma Profilingsupporting
confidence: 80%
“…The kinetic triplets were calculated for the whole process 30-800 • C and the decomposition peaks. The first peak in both samples is related to water and light volatile organic constituents' removal [61]. The second peak is related to the main decomposition of compounds that were described in the previous paragraphs.…”
Section: Peat Thermal Decomposition Kinetics By Coats-redfernmentioning
confidence: 69%